Effect of exchange rate changes on trade balance and domestic production in Malaysia - Kamaluddin, Farween (2020)
This thesis attempts to investigate the effect of exchange rate changes on the bilateral trade balance and the domestic production of Malaysia. The first issue of this study examines the impact of exchange rate changes on the bilateral trade balance of Malaysia with its 6 major trading partners. Most of the previous studies that have assessed the short-run and the long-run effects of exchange rate changes on trade balances relied upon linear adjustment processes with assorted outcomes. However, the recent innovations in the co-integration analysis has allowed for estimations from the perspective of a nonlinear relationship. In this study, the appreciation is separated from depreciation of exchange rate through the partial sum concept and thereby nonlinearity is introduced into the model to demonstrate the asymmetric effect of exchange rate changes on the bilateral trade balance. By applying the nonlinear ARDL method of Shin et al. (2014), the results discover short-run and long-run asymmetric effects of exchange rate changes on the Malaysian trade balance, particularly with China, Hong Kong, Singapore and the US. Several policy implications can be derived from the findings such as bilateral level studies give out more country-specific findings and the nonlinear model plays an important role in differentiating the effects of appreciations from depreciations. The second issue, investigates the effects of exchange rate changes on the domestic production of Malaysia. Currency depreciation is expected to have positive or negative effects on domestic production. By separating ringgit appreciation from its depreciation using the partial sum concept, nonlinearity is introduced into the model to show that the effect of exchange rate changes on domestic production is asymmetric. Using the nonlinear ARDL model of Shin et al. (2014), the results show that the exchange rate changes do have asymmetric effect on the domestic production. In the short-run, both ringgit appreciation and depreciation have expansionary effects. Meanwhile in the long-run, ringgit appreciation appeared to be contractionary while ringgit depreciation expansionary. This suggests that exchange rate played a key role in Malaysian domestic production process. The policy implications derived from this study are that the monetary and fiscal policies have been fruitful in developing the domestic output, the supply side are crucial in reducing cost of productions and the government should policies that can monitor the exchange rate behavior.